Antimicrobial Activity and Phytochemical Characterization of Baccharis Concava Pers., a Native Plant of the Central Chilean Coast - Martinez-Salinas, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Few sclerophyllous plants from the central coast of Chile have been systematically studied. This work describes the phytochemical composition and antimicrobial properties of Baccharis concava Pers. (sin. B. macraei), a shrub found in the first line and near the Pacific coast. B. concava has been traditionally used by indigenous inhabitants of today’s central Chile for its medicinal properties. Few reports exist regarding the phytochemistry characterization and biological activities of B. concava. A hydroalcoholic extract of B. concava was prepared from leaves and small branches. Qualitative phytochemical characterization indicated the presence of alkaloids, steroids, terpenoids, flavonoids, phenolic, and tannin compounds. The antimicrobial activity of this extract was assessed in a panel of microorganisms including Gram-positive bacteria, Gram-negative bacteria, and pathogenic yeasts. The extract displayed an important antimicrobial effect against Gram-positive bacteria, Candida albicans, and Cryptococcus neoformans but not against Gram-negatives, for which an intact Lipopolysaccharide is apparently the determinant of resistance to B. concava extracts. The hydroalcoholic extract was then fractionated through a Sephadex LH-20/methanol–ethyl acetate column. Afterward, the fractions were pooled according to a similar pattern visualized by TLC/UV analysis. Fractions obtained by this criterion were assessed for their antimicrobial activity against Staphylococcus aureus. The fraction presenting the most antimicrobial activity was HPLC-ESI-MS/MS, obtaining molecules related to caffeoylquinic acid, dicaffeoylquinic acid, and quercetin, among others. In conclusion, the extracts of B. concava showed strong antimicrobial activity, probably due to the presence of metabolites derived from phenolic acids, such as caffeoylquinic acid, and flavonoids, such as quercetin, which in turn could be responsible for helping with wound healing. In addition, the development of antimicrobial therapies based on the molecules found in B. concava could help to combat infection caused by pathogenic yeasts and Gram-positive bacteria, without affecting the Gram-negative microbiota. © 2024 by the authors.